High School Students' Understanding of Personal Betrayal in a Socio-Historical Context of Ethnic Conflict: Implications for Teaching History. (1st August 2011) - Bellino, Michelle; Selman, Robert
Research in history education frequently characterizes evaluative judgments of past events as ahistorical applications of contemporary ethical standards, citing "presentism" as a hindrance to disciplinary thinking. In accordance with this view, much of the recent educational research exploring adolescents' capacity to understand human agency in past contexts has focused on their ability to cognitively interpret historical perspectives while minimizing the opportunity for evaluative components of those decisions. But little work has focused on how adolescents understand decision-making in historical contexts of conflict, where socio-historical understanding implies ethical reflection on the part of the historical agents. In this paper, we focus on one component of a new measure designed to assess adolescent historical understanding, where issues of intolerance and injustice are dominant (or "purposeful") parts of the historical narrative to be understood. The authors analyzed the responses of the control sample of a national evaluation study (n=621), in which ninth and tenth grade students considered why one friend might betray another during a period of ethnic and religious conflict in the former Yugoslavia. Despite the risk of reinforcing the natural tendency to apply presentistic thinking to historical actors, our findings suggest that when asked for a descriptive interpretation of human agency, a significant number of participants in this study grappled with moral agency, not only from the perspective of historical actors, but also as moral agents in the present. We contextualize these findings within the pedagogical debate on the degree to which historical cases of social injustice can be taught in a way that helps students to integrate their natural inclination for ethical reflection with the intellectual rigor required of historical understanding.